Growth Profit In Islamic Commercial Banks Registered In The Indonesia Financial Services Authority With The Camel Ratio - Nasser Hasibuan, Abdul; Hardana, Ali; Windari, Windari; Efendi Siregar, Sulaiman; Harahap, Halimatussadiah (Proceedings of International Conference on Islamic Economic Finance and Social Finance (ISSN: XXXX-XXXX) (ESSN: XXXX-XXXX), 2023)
This study covers all Islamic commercial banks registered with the Financial Services Authority from 2015 to 2018. The population of the study includes all Islamic commercial banks registered with the Financial Services Authority from 2015 to 2018. Factors influenced by the capital suitability ratio, capital suitability ratio, return on assets ratio, and capital suitability ratio. The purposive sampling method was used in the sampling technique. 9 companies were obtained based on predetermined criteria. Secondary data used came from the Financial Services Authority website and each Islamic commercial bank. Panel data logical regression analysis was used. The results showed that Capital proxied by CAR, Management proxied by NPM, and Earnings proxied by ROA had a positive effect on Profit Growth, while Asset Quality proxied by NPF and Liquidity proxied by FDR had no effect on Profit Growth.